2021
DOI: 10.1002/car.2732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Trauma‐Informed Mental Health Assessment Measures in Care Planning for Children and Adolescents in Out‐of‐Home Residential Care in Singapore

Abstract: Children and young people (CYP) within the Child Welfare System (CWS) often experience a range of trauma‐related difficulties. However, systematic use of evidence‐based measures to support mental health assessment and care planning appeared to be lacking within CWS in Singapore. This study evaluated the use of evidence‐based measures to inform care planning in out‐of‐home residential care in Singapore. Participants were 65 CYP in care. Measures consisted of the Child PTSD Symptom Scale for DSM‐5 (CPSS‐5), Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Zhu et al (2023) also studied 874 children in Japan and found statistically significant differences between their negative experiences and emotional problems. In another study carried out in Singapore, Peh et al (2022) found the prevalence of PTSD in out of home care children to be 23.1% and the prevalence of emotional problems to be 7.7%). Peer problems could be due to poor parenting and insecure attachments which are the basis for relationships with the world ( Van et al, 2022).…”
Section: Discussion Of Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Zhu et al (2023) also studied 874 children in Japan and found statistically significant differences between their negative experiences and emotional problems. In another study carried out in Singapore, Peh et al (2022) found the prevalence of PTSD in out of home care children to be 23.1% and the prevalence of emotional problems to be 7.7%). Peer problems could be due to poor parenting and insecure attachments which are the basis for relationships with the world ( Van et al, 2022).…”
Section: Discussion Of Resultsmentioning
confidence: 92%
“…Most are rescued from abusive situations, poor parenting, and neglect hence mental and behaviors needs from the largest percentage of their health needs (American Academy of Pediatrics, 2021;Font & Gershoff, 2020;Kim et al, 2021;Suh et al, 2020). In Singapore, children and young people in out of home care have gone through adverse experiences and have been reported to have symptoms of post-traumatic stress disorders, depression, anxiety, and conduct problems (Peh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%